Uniform growth of MoS2 films using ultra-low MoO3 precursor in one-step heating chemical vapor deposition - Sirat, Mohamad Shukri; Johari, Muhammad Hilmi; Mohmad, Abdul Rahman; Mohammad Haniff, Muhammad Aniq Shazni; Ani, Mohd Hanafi; Syono, Mohd Ismahadi; Mohamed, Mohd Ambri (Elsevier, 2022)
In chemical vapor deposition (CVD), homogeneous molybdenum vapor concentration is important in synthe- sizing uniform thickness and large coverage of two-dimensional molybdenum disulfide (2D-MoS2) films. Here, we synthesize few-layer MoS2 films with uniform thickness and adequate coverage over 50 mm2 size area using ultra-low molybdenum trioxide (MoO3) precursor placed directly under a face-down silicon dioxide/silicon (SiO2/Si) substrate in one-step heating CVD. The precursor mass is controlled by dispersing MoO3 powder in ethanol (C2H5OH) and varying the volume of MoO3/C2H5OH solution coated on SiO2/Si substrates into 10, 20 and 25 μL. Field emission scanning electron microscopy images reveal that 20 μL MoO3/C2H5OH solution pro- duces ~93% area coverage of 2D-MoS2 films. The average Raman spectra show the typical presence of MoS2 peaks around 378.8 cm− 1 and 404 cm− 1 referring to the E12g and A1g modes, respectively. The difference be- tween the two Raman modes for all samples is ~25 cm− 1, indicating few-layer MoS2 films. The thickness of MoS2 films is estimated at around 2.8 ± 0.44 nm and 3.2 ± 0.43 nm (~6 layers) using atomic force microscopy analysis. These findings suggest that ultra-low MoO3 precursor is useful to produce uniform thickness and high coverage few-layer MoS2 films using one-step heating CVD.